OP13 The changing prevalence of births after subfertility and fertility treatment in england 1991–2013: evidence from the clinical practice research datalink. (2nd September 2017) - Carson, C; Quigley, MA; Kurinczuk, JJ; Bankhead, C; Stevens, S
Abstract : Background: We describe the prevalence of births after subfertility and fertility treatment seen in primary care in England between 1991 and 2013 and and examine the impact of changing maternal characteristics over time. Methods: Data from the Clinical Practice Research Datalink (CPRD) Mother-Baby dataset were used, comprising records from >600 general practices across England, linked to index of multiple deprivation (IMD). 4 40 623 mothers registered for > 18 months prior to the birth of their child were included; 2 39 781 first-time mothers were analysed separately to assess changes in primary infertility. Fertility history was identified using details of diagnoses, referrals and prescriptions in GP records, and grouped as: 'no evidence of fertility problems' and 'any subfertility' (comprising 'untreated', 'ovulation induction' (OI), and 'Assisted Reproductive Technologies' (ART), such as IVF). Change in the prevalence of births by fertility group and population characteristics was assessed using chi-squared trend tests. Direct age-standardisation (to 1991 study population) accounted for changing population structure. Results: Overall, 4.7% of mothers experienced subfertility (1991: 1.7%–2013: 6.3%), comprising: untreated 2.6% (1991: 0.6%–2013: 3.5%), OI 0.8% (1991: 0.6%; peaking in 1995: 1.3%; 2013: 0.5%), and ART 1.3% (1991: 0.5%–2013: 2.4%) (all p<0.001 for trend). Women now tend to have children later – 13.5% of mothers were >35 years in 1991, rising to 27% by 2013. Age-adjusted 2013 figures were 3.1%, 1.8%, 0.2% and 1.1%, for all, untreated, OI and ART respectively. 6.6% of first-time mothers experienced subfertility (1991: 2.1%–2013: 9.7%): comprising untreated 3.6% (1991: 0.8%–2013: 5.2%), OI 1.0% (1991: 0.7%–2013: 0.6%), and ART 2.0% (1991: 0.7%–2013: 3.9%) (all p<0.001 for trend). Age-adjusted 2013 figures were 7.0%, 3.9%, 0.4%and 2.7%, for all, untreated, OI and ART respectively. Subfertility was more prevalent in more advantaged women, with growing disparity suggested (age-adjusted 2.1% in IMD1 vs 1.3% in IMD5 in 1991, increasing to 5.1% vs 1.4% by 2013). Discussion: Births to women with records of fertility problems have significantly increased between 1991 and 2013. Changes in maternal age explain much of the population-level trends, but less of the observed increase among first-time mothers. Declining births after OI prescribed in primary care may reflect changing management of patients. Medical advice must continue to highlight the effect of age on fertility, and the implications for secondary infertility. GPs and service commissioners should be aware that time trends indicate continuing growth in demand for fertility treatment in England.